Post-Retirement Career Development Strategy for Civil Servants in the Ministry of Transportation in East Java Province: Analysis and Implementation - Sukanti Swastikawati; Sri Utami Ady (Jurnal Indonesia Sosial Sains, 2024)
Many civil servants in the Ministry of Transportation face challenges in determining their career direction after retirement. The lack of preparation and post-retirement career plans can become a problem that needs to be addressed. This study aims to identify and analyze post-retirement career development strategies for Civil Servants (PNS) at the Ministry of Transportation in East Java Province, as well as their implementation in improving the welfare and satisfaction of civil servants after retirement. The method used was an observational research design with a cross-sectional approach, collecting data through surveys and interviews from civil servants who are about to retire or have retired. The study revealed that strategies such as skills development, mentoring, and entrepreneurship programs have a significant positive impact on civil servants' retirement readiness and quality of life. The findings contribute to the human resource management literature and offer practical guidance for government agencies in supporting civil servants' career transition post-retirement.